Analisis Yuridis Keabsahan Perjanjian Kerja Sama Endorsement dalam Perspektif KUH Perdata - Renti Astuti; Lona Puspita (Normative Jurnal Ilmiah Hukum, 2026)
The rapid shift toward a fully digital era has given rise to a form of product marketing collaboration that leverages social media platforms and content creators to promote goods or services through original content. While endorsements have evolved into a practical marketing strategy, the absence of specific regulations creates potential legal issues regarding their validity; thus, this study aims to analyze the forms, validity, and legal consequences of these arrangements—specifically through the lens of the requirements for a valid contract under civil law—to address the existing regulatory gap. Conducted as normative legal research employing statutory and conceptual approaches, the study gathered data via literature review and utilized descriptive analysis. The findings indicate that, under the Indonesian Civil Code, endorsement collaboration agreements are classified as "innominate contracts" (contracts not specifically named in the Code)—an implementation of the principle of freedom of contract within an open system—which give rise to specific rights and obligations. There is no requirement for such collaborations to be in writing to be legally binding; broadly speaking, endorsement agreements can take three primary forms—formal written, informal written, and oral—each offering varying degrees of legal certainty. An agreement is deemed valid if it meets the requirements set forth in Article 1320 of the Civil Code; however, these requirements cannot be interpreted or applied in a narrow or isolated manner, as they are interconnected and mutually influential.